Three-Phase High Power Underwater Capacitive Wireless Power Transfer System for Autonomous Underwater Vehicles - Lei Yang; Liye Tian; Xinze Chen; Zhixue Bu; Dengrui Xing; Aimin Zhang; Xiangqian Tong (Journal of Marine Science and Engineering)
This paper proposes a 1000 W high-frequency three-phase power inversion underwater capacitive wireless power transfer (UCWPT) system for power delivery to autonomous underwater vehicles (AUVs). The multi-phase coupling structure is designed as a columnar configuration that conforms to the shape of AUVs. This paper innovatively presents a curved coupling coupler composed of six metal plates. This design significantly enhances the mutual capacitance of the coupling structure and the power transfer capacity of the UCWPT system. Utilizing the columnar structure, the receiver of the capacitive wireless power transfer system can be easily integrated into AUVs, reducing the installation space. Furthermore, the cylindrical dock-transmitter terminal structure of the system greatly improves the anti-misalignment capability. This addresses issues such as charging voltage and current fluctuations caused by vehicle rolling in dynamic ocean environments. Additionally, the wireless power transfer capacity is notably enhanced. An experimental platform was constructed, and tests were conducted in both air and water media. A 1000 W experimental setup was developed to validate the theoretical analysis and simulations. The experimental results align closely with the theoretical predictions. At a fixed distance of 3 cm between transmitter and receiver, peak power transfer efficiencies of 80% in air and 74% in water were achieved with stable operational performance. The cylindrical structure demonstrates robust anti-misalignment properties.